Inscribing Faith: Students’ Portrayal of Islamic Beliefs in Writing - Kurniawan, Redite; Zulkarnain, (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
This study explores the dynamic interplay between religious education and students' expressive writing, focusing on the diverse ways in which their faith is manifested in their written reflections. It examines the impact of Aqidah Akhlaq lessons on students' religious expression, taking into account the influence of the madrasah educational environment, individual differences, and societal factors. Data were collected from a cohort of 24 ninth-grade students at MTs. Integrated Ar-Roihan Lawang Malang, comprising both female and male participants, and analyzed to identify patterns of religious expression across two sample writing sessions. The findings highlight various dimensions of religious expression, including direct relationships with Allah, reflections on Islamic teachings, ethical values, and spiritual devotion. The influence of religious knowledge on expression is underscored, as students' understanding deepens and authenticates their faith-based articulations. The results indicate that religious education nurtures linguistic proficiency, thoughtful contemplation, and alignment with Islamic moral values. Future research directions are proposed to explore the impact of different educational contexts on religious expression in students' expressive writing.